Tax Distortion, Countervailing Subsidies and Income Redistribution - Salvatore Barbaro (Georg-August-Universität Göttingen, Volkswirtschaftliches Seminar, 2004)
A persistent controversy in the economics of higher education is the distributional consequences of tuition-fee subsidies. There are two points at issue. First, subsidies affect income distribution between rich and poor households, analyzed by cross-sectional studies. Second, there may also be long-run effects on income distribution, i.e., toward graduates who benefited from public higher education and away from non-graduates who contributed their taxes to finance these subsidies. This paper focuses on whether it is in the interest of the non-graduates to subsidize investments in higher education. We show that subsidies to higher education may be Pareto-superior, benefiting all agents rather than the minority of graduates alone. However, it is also likely that efficiency gains cannot be distributed among all agents if a large fraction of agents uses subsidies to reap windfall gains. Windfall gains occur because of the unavailability of agents' endowments and are identified as the main cause of unwanted distributional effects between graduates and non-graduates. Nevertheless, it would be possible to establish a voluntary graduate tax that works as a revelation mechanism and, consequently, breaks down the equity-efficiency trade-off.
Keywords: I22; H22; H21; 330; tax distortion; voluntary graduate tax; income redistribution; Studium; Bildungsfinanzierung; Subvention; Einkommensverteilung; Einkommensteuer; Akademische Berufe; Optimale Verteilung; Windfall Profit; Theorie; graduate tax